Middle Lobe Syndrome Associated with Bronchial Anthracofibrosis - Gonlugur, Ugur; Gonlugur, Tanseli; Ozer, Sule (Acta medica Lituanica, 2020)
Bronchial anthracofibrosis has been defined as airway narrowing associated with dark pigmentation on bronchoscopy without an appropriate history of pneumoconiosis or smoking. We present a case of a 67-year-old, non-smoking female patient who was referred to our clinic for two years of persistent cough. Spirometry was within normal limits. Radiological evaluation showed right middle lobe atelectasis and positron emission tomography-positive mediastinal lymph nodes. Bronchoscopy revealed black airway discoloration and distortions. In conclusion, we propose monthly radiological controls before an invasive procedure in such cases if a strong suspicion of malignancy/tuberculosis is not present.